2017
DOI: 10.3390/su9081451
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Depth, Vegetation and Irrigation Affect Green Roof Thermal Performance in a Mediterranean Type Climate

Abstract: Green roofs are consistently being used to reduce some of the negative environmental impacts of cities. The increasing interest in extensive green roofs requires refined studies on their design and operation, and on the effects of their relevant parameters on green roof thermal performance. The effects of two design parameters, substrate thickness (ST) and conductivity of dry soil (CDS), and four operating parameters, leaf area index (LAI), leaf reflectivity (LR), stomatal resistance (SR), and moisture content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…In their study in Toronto, Liu et al [38] also observed a similar effect due to heat loss reduction. Overall, the obtained results were discreet due to the high insulation of the building [25,26], to the relatively early stage of the vegetation development, and the winter season when in general, fewer differences can be observed [24].…”
Section: Discussion Over the Obtained Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In their study in Toronto, Liu et al [38] also observed a similar effect due to heat loss reduction. Overall, the obtained results were discreet due to the high insulation of the building [25,26], to the relatively early stage of the vegetation development, and the winter season when in general, fewer differences can be observed [24].…”
Section: Discussion Over the Obtained Resultsmentioning
confidence: 94%
“…The proper specification is essential for designing an effective system. Local boundary conditions such as air temperature, relative humidity, incoming solar radiation, rain incidence, and of course the overall stratigraphy, and materials contribute to the thermal transmittance of the construction skin, and play a crucial role for the effectiveness of the roof [3,24]. Some authors discuss that for highly insulated buildings and low heating demand, the thermal effects of the green roofs are not relevant [5,7,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the total runoff volume will be largely determined by the total amount and intensity of precipitation. On the other hand, many studies agree that the soil type and its properties, including the type of vegetation, has a greater influence on green roof water retention capacity [41,42,51]. In this sense, the type of vegetation commercially available for non-intensive green roofs is very limited, with grass or sedum being practically the only commercial options.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the design and operational conditions of green roofs, experimental investigations unveiled that the operating parameter of moisture content and the designing parameter of substrate thickness reduce the substrate temperature and heat flux through the green roof, thus, consistently reducing some of the negative environmental impacts of built environments [59], generating considerable energy savings, improving the thermal performances of buildings, as well as substantially improving the dynamic properties of traditional roof structures, especially in the case of roofs with limited dynamic performances [60].…”
Section: Parameters Of Cost Reductionmentioning
confidence: 99%